Is Love Addiction Always Detrimental? Evidence from Romantic Satisfaction in Early Adults - Puhi, Sitti Rojiyah Nur Insyirah (program studi psikologi, 2025)
Romantic relationships play an important role in fulfilling emotional needs during early adulthood. One factor influencing relationship dynamics is love addiction, characterized by intense emotional attachment to a romantic partner. This study aimed to examine the relationship between love addiction and romantic satisfaction among individuals aged 18–30 years. A quantitative correlational design was employed. Participants were early adults currently involved in a romantic relationship. Data were collected using the Love Addiction Inventory (LAI) to assess levels of love addiction and the Couples Satisfaction Index (CSI-16) to measure romantic satisfaction. Statistical correlation analysis was conducted to test the relationship between variables. The results revealed a significant positive relationship between love addiction and romantic satisfaction, indicating that higher levels of love addiction were associated with greater satisfaction in romantic relationships. These findings suggest that, within the context of early adulthood, love addiction may be perceived as an intense form of emotional attachment that contributes positively to relationship satisfaction. This study provides empirical insight into romantic relationship dynamics and offers a foundation for future research on the adaptive and maladaptive aspects of love addiction.